A randomized controlled pilot trial to assess the effectiveness of a specially formulated food supplement and pelvic floor muscle training in women with stress-predominant urinary incontinence - Peter Takacs; Krisztina Pákozdy; Erzsébet Koroknai; Balázs Erdődi; Zoárd Krasznai; Bence Kozma (BMC Women's Health, 2023)
Abstract Background Pelvic floor muscle training (PFMT) is the first-line treatment approach for stress urinary incontinence. Creatine and leucine have been shown to improve muscle function. Our aim was to assess the effectiveness of a food supplement and PFMT in women with stress-predominant urinary incontinence. Methods Women with stress-predominant urinary incontinence were randomized in 1:1 ratio to receive daily oral supplementation for six weeks with either a food supplement (treatment group) or placebo (control group). Both groups were instructed to perform standardized daily PFMT. The primary outcome was the Urogenital Distress Inventory Short Form (UDI-6) score. Secondary outcomes were the Incontinence Impact Questionnaire (IIQ-7) score, Patient’s Global Impression of Severity (PGI‐S), and Biomechanical Integrity score (BI-score) measured by Vaginal Tactile Imager. To have a power of 80% and a significance level of 5% to detect a decrease of 16 points in the UDI-6 score, a sample size of 32 was needed, with 16 patients in each arm of our trial. Results Sixteen women in the control group and sixteen in the treatment group completed the trial. Between-group analysis revealed no significant differences between the control and treatment group except for mean change (delta) in vaginal squeeze pressure [(cmH2O, mean ± SD), 5 ± 12 vs. 15 ± 15, P = 0.04] and mean change (delta) in PGI-S score [(mean ± SD), -0.2 ± 0.9 vs. -0.8 ± 0.8, P = 0.04]. Within-group analysis showed that UDI-6 and IIQ-7 scores improved significantly from baseline to six weeks in the treatment group but not in the control group [UDI-6 score (mean ± SD) 45 ± 21 vs. 29 ± 21, P = 0.02; 43 ± 18 vs. 33 ± 26, P = 0.22] [IIQ-7 score (mean ± SD) 50 ± 30 vs. 30 ± 21, P = 0.01; 48 ± 23 vs.40 ± 28, P = 0.36]. PGI-S scores only improved in the treatment group from baseline to six weeks after treatment [PGI-S score (mean ± SD) 3.1 ± 0.8 vs. 2.3 ± 0.8, P = 0.0001]. BI-score, on average, improved significantly in the treatment and control group as well [SD unit, mean, from − 1.06 to -0.58, P = 0.001; from − 0.66 to -0.42, P = 0.04]. Conclusions Women with stress-predominant urinary incontinence receiving a specially formulated supplement in addition to daily PFMT for six weeks had significantly improved urinary symptoms (decrease in UDI-6 score and IIQ-7) and BI-score compared to their baseline. Trial registration ClinicalTrials.gov Identifier: NCT05358769. 27/04/2022.